Nest architecture of Oxaea austera (Andrenidae, Oxaeinae) and its significance for the interpretation of Uruguayan fossil bee cells - Sarzetti, Laura Cristina (2014)
Oxaea austera nests in hard, red lateritic soils with dense grass cover. Some characters of Oxaea austera nests conform to the known architecture of the oxaeine nests such as the long, vertical shaft and the radiating, horizontal tunnels connected to vertical cells. The presence of more than one cell per lateral, cells at different depths containing larvae at different stages, and discrete walls in the main and laterals are described for the first time for Oxaeinae. One cell was located at the end of each lateral with others (2–4) near them, in some cases arranged in a row just beneath the lateral. Cells are oriented vertically and consist of a chamber, a spiral closure and an antechamber connected with a lateral. The chamber and antechamber are surrounded by a thick discrete wall. Each nest was occupied by at least two active females indicating communal nesting. They also contained older cells, suggesting the reutilization of the nests by successive generations. Both behaviors may be a response to the difficulties of excavation in hard soils. Communal nesting may be also a defensive behavior against nest cleptoparasites. The shape, size, discrete walls of lateritic soil material, spiral closure, and antechamber of O. austera cells closely resemble the fossil bee cells included in the ichnogenus Palmiraichnus from the early Eocene Asencio Formation of Uruguay. This new evidence reinforces the proposal of extinct representatives of Oxaeinae as it constructor.